2016
DOI: 10.21273/horttech.26.4.444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antitranspirants for Enhancing Temporary Water Stress Tolerance in Bedding Plants

Abstract: Water stress during shipping and retailing reduces the postproduction quality and marketability of bedding plants. Antitranspirants can temporarily prevent plants from wilting by either physically blocking stomata or physiologically inducing stomatal closure, limiting transpirational water loss from leaves. The goal of this research was to evaluate the efficacy of commercially available antitranspirants on enhancing temporary water stress tolerance in bedding plants. Two physical antitranspirants [β-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…To address this need, products such as chitosan should be evaluated. Chitosan is a naturally derived antitranspirant that has been shown to elicit plant defense mechanisms resulting in stomatal closure and reduction in transpiration (Bittelli et al, 2001; Iriti et al, 2009Park et al, 2016). Joy (2010) observed that when chitosan was applied as a foliar antitranspirant to self-grafted 'Cherokee Purple' tomato under two RH treatments (37% and 95%), chitosan-treated plants had 30% higher survival than nontreated plants at both levels of RH on day 10 (when plants were fully acclimated).…”
Section: Discussionmentioning
confidence: 99%
“…To address this need, products such as chitosan should be evaluated. Chitosan is a naturally derived antitranspirant that has been shown to elicit plant defense mechanisms resulting in stomatal closure and reduction in transpiration (Bittelli et al, 2001; Iriti et al, 2009Park et al, 2016). Joy (2010) observed that when chitosan was applied as a foliar antitranspirant to self-grafted 'Cherokee Purple' tomato under two RH treatments (37% and 95%), chitosan-treated plants had 30% higher survival than nontreated plants at both levels of RH on day 10 (when plants were fully acclimated).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Agehara and Leskovar (2012) reported that stomatal limitation to photosynthesis by exogenous abscisic acid limited shoot dry matter accumulation in muskmelon seedlings. Other negative side effects of abscisic acid include leaf chlorosis, leaf abscission, and excessive inhibition in leaf expansion and stem elongation (Agehara and Leskovar, 2014aLeskovar, , 2014bLeskovar, , 2015Leskovar, , 2017Park et al, 2016). In addition, the performance of film-forming antitranspirants is limited primarily on the adaxial leaf surface and is dependent highly on spray coverage (Goreta et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Many chemical compounds have been evaluated for their effectiveness in reducing transplant shock (Berkowitz and Rabin, 1988;del Amor et al, 2010;Goreta et al, 2007;Iriti et al, 2009;Moftah and Al-Humaid, 2005). Antitranspirants can reduce plant water loss by limiting transpiration physically or physiologically (Park et al, 2016). The most popularly used physical antitranspirants are spray emulsions of latex, wax, or acrylic that form thin films over leaf surfaces and block stomata (Park et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A balance between leaf photosynthesis and transpiration can be achieved by adjusting the stomatal behavior to the optimal status using exogenous substances (antitranspirants), which lead to an increase in water use efficiency (WUE) at the leaf level. Also, antitranspirants can increase leaf superoxide dismutase (SOD) and peroxidase (POD) activities to improve drought resistance in crops [3][4][5][6][7][8] , and alleviate the negative effects of drought on crop production [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%